Speak - Anderson, Laurie Halse (New York : Speak, 2006)
A traumatic event near the end of the summer has a devastating effect on Melinda's freshman year in high school. Includes bonus material and a new forward by the author.
School Library Journal starred.
Wilson's Junior High School.
Wilson's Senior High School.
Young Adult
Keywords: Emotional problems of teenagers -- Juvenile fiction; High schools -- Juvenile fiction; Rape -- Juvenile fiction; Schools -- Juvenile fiction; Emotional problems -- Fiction; High schools -- Fiction; Psychological fiction; Rape -- Fiction; Schools -- Fiction; Emotional problems -- Fiction; High schools -- Fiction; Psychological fiction; Rape -- Fiction; School stories; Psychological fiction